ENGLISH AND KARAKALPAK COLOUR IDIOMS AND THEIR CLASSIFICTIONS (American Journal of Interdisciplinary Research and Development, 2022)
This study provides  the usage, classification of Colour idioms in comparative ways illustrating with the examples. The most common colour idiom such as black is defined with a wide range of concepts along with structure.